Empirical Analysis of Firms' Willingness to Participate in Infrastructure PPP Projects - Ye, X.; Shi, S.; Chong, Heap Yih; Fu, X.; Liu, L.; He, Q. (American Society of Civil Engineers, 2018)
Private participation is the key element in forming a public-private partnership (PPP). Numerous studies have identified the factors of private participation in infrastructure projects, but the results have rarely focused on the willingness of the private sector to participate in infrastructure PPP projects. This research examines the factors of the private participation in a PPP with the consideration of the willingness to participate as a function of internal (e.g., the firm's nature) and external factors (e.g., institutions, the government's behavior, and project characteristics). Using the logistic regression model and the data from a questionnaire survey, this research found that nine variables have a significant coefficient, e.g., profitability, political connections, government intervention, government support, project complexity, and project experience; in particular, those companies with more project experience, more political connections, and higher profitability are more likely to be willing to participate in PPP projects. In contrast to previous studies, this research finds no support for the effect of the institutional environment and public support on a firm's willingness to participate in PPPs. These findings can serve as a valuable reference in shaping the private sector's motivation to participate in PPPs. The factors of private participation in PPP projects are explained and discussed in the context of the Chinese PPP experience and practice.